Tissue Rheology as a Possible Complementary Procedure to Advance Histological Diagnosis of Colon Cancer - Deptuła, Piotr (ACS Biomater Sci Eng, 2020)
[Image: see text] In recent years, rheological measurements of cells and tissues at physiological and pathological stages have become an essential method to determine how forces and changes in mechanical properties contribute to disease development and progression, but there is no standardization of this procedure so far. In this study, we evaluate the potential of nanoscale atomic force microscopy (AFM) and macroscopic shear rheometry to assess the mechanical properties of healthy and cancerous human colon tissues. The direct comparison of tissue mechanical behavior under uniaxial and shear deformation shows that cancerous tissues not only are stiffer compared to healthy tissue but also respond differently when shear and compressive stresses are applied. These results suggest that rheological parameters can be useful measures of colon cancer mechanopathology. Additionally, we extend the list of biological materials exhibiting compressional stiffening and shear weakening effects to human colon tumors. These mechanical responses might be promising mechanomarkers and become part of the new procedures in colon cancer diagnosis. Enrichment of histopathological grading with rheological assessment of tissue mechanical properties will potentially allow more accurate colon cancer diagnosis and improve prognosis.